ECONOMIC JUSTIFICATION FOR FLORICULTURE DEVELOPMENT IN SERBIA - Vukajlović, Đurđica Đ.; van Veghel, Hugo; Đurović, Slobodan Đ. Đ. (Economics of Agriculture, 2017)
Floriculture is a part of horticulture, an agricultural activity which has been on the rise during the past decades. It is different from traditional culture, not only due to the increased sales revenues, but also because flowers are ever more present in daily life, which has created opportunities for engaging in floriculture as a legitimate source of income. The aim of the paper is to present the current situation in the area of floriculture in the world and in Serbia, as well as to draw attention to the relationship between the import and export of floriculture products. This paper includes a SWOT analysis that provides an overview of the current state of floriculture in Serbia and the opportunities for its development. Floriculture is not widespread in Serbia, even though there are quite advantageous climatic conditions, fertile land, tradition and experience, but not enough innovation, inadequate equipment, technological lagging behind in production and insuffcient harmonization with EU standards.